Enhanced visible photocatalytic degradation of diclofen over N-doped TiO2 assisted with H2O2: A kinetic and pathway study - Thang Phan Nguyen (Arabian Journal of Chemistry, 2020)
Increasing discharge and inadequate removal of pharmaceutical compounds pose significant concerns over global aquatic systems and human health. The accomplishment of affordable and safe water requires a stringent elimination of these micropollutants. This study evaluated the performance of Visible/N-doped TiO2 and Visible/N-doped TiO2/H2O2 processes using a submerged photocatalytic membrane reactor (SMPR) with suspended N-doped TiO2 to address the removal of diclofenac (DCF). The kinetic and pathway of photodegradation of DCF were of particular interest in this study. The initial DCF concentrations upon the experiments were also examined using a wide range of 5–50 mg/L and 20–100 mg L−1 for Vis/N-doped TiO2, and Vis/N-doped TiO2/H2O2 process, respectively. The results indicated that higher initial concentration reduces the efficiency of the process, but one with H2O2 demonstrated an enhanced performance. The experimental data were found to fit well a pseudo-first-order kinetic model. Our findings demonstrated the analogous pathways of DCF for both processes. The Vis/N-doped TiO2/H2O2 process tends to hasten the degradation rate as evidenced by the disappearance of some DCF byproducts at a similar irradiation period as compared to the other. The study provided useful information of the degradation rate and the potential formation of DCF intermediates upon the hybrid photocatalytic systems, therefore being of importance for scaling-up as well as evaluating potential detoxification of DCF upon the novel photocatalytic system.